(untitled) (Research, Society and Development, 2023)
Introduction Emery-Dreifuss muscular dystrophy is a rare genetic disease and corresponds to the fourth leading cause of muscular dystrophy in the world. It can be caused by mutations in several genes, including EMD, leading to a defect in the production of the emerin protein and is clinically characterized by the classic triad of muscle weakness, joint contractures and heart disease. Objective To describe two cases diagnosed with Emery-Dreifuss muscular dystrophy resulting from a new mutation in the EMD gene. Methodology Two case reports with the new mutation were described, comparing them with 148 cases in the literature after a narrative review. Results Despite the natural history of the disease being similar to the classic picture of Emery-Dreifuss muscular dystrophy, there was a greater presence of atypical symptoms than those already commonly described in the literature, especially facial involvement. Conclusion The identification of a new variant in the mutation of the EMD gene allows for a more accurate diagnosis of Emery-Dreifuss muscular dystrophy, in addition to allowing, during follow-up, the identification of different spectrums of systemic impairment related to the disease.